1980
DOI: 10.1002/cne.901930302
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the face representation in macaque motor cortex

Abstract: We stimulated with microelectrodes the face representation in precentral motor cortex in macaque monkeys. Responses were very discrete; at threshold current levels the usual response was a small focus of movement in part of a muscle. Facial muscles cluster together in the posterior and anterior portions of the precentral gyrus with tongue movements represented in the intervening region and along the lateral extent. Within each cluster there are multiple representations of individual muscle movements. In long p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 20 publications
4
44
1
Order By: Relevance
“…9). This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 92%
See 1 more Smart Citation
“…9). This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 92%
“…However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…At lateral levels, callosal cells occupied almost the entire rostrocaudal extent of the frontal lobe, from the cortex of the more superficial part of the posterior bank of the arcuate sulcus (AS; area 6) to that buried in the rostra1 bank of the central sulcus (CS; area 4). This region, which contains the representations of orofacial structures (Woolsey et al, 1950;Clark and Luschei, 1974;Muakkassa and Strick, 1979;McGuinnes et al, 1980;Sessle and Wiesendanger, 1982;Gould et al, 1986;Matelli et al, 1986), was devoid of frontoparietal association neurons. Gould et al (1986) described in the owl Figure 3.…”
Section: Tangential Distribution Of Callosal and Association Neuronsmentioning
confidence: 99%
“…Rather than representing individual muscles or small muscle groups in a topographic fashion (Asanuma and Rosen, 1972;McGuinness et al, 1980), multiple lines of evidence indicated that motor cortex was organized as a mosaic, with body parts represented multiple times in a gross topographic order (Gould et al, 1986). Subsequently, an alternative scheme has emerged in macaque monkeys with motor cortex composed of ethologically relevant, complex movement domains overlaid upon a simple, grossly topographic map of the body (Graziano et al, 2002;Cooke and Graziano, 2004;Graziano et al, 2005;Maranesi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%